VD_FINDINFO AI 424/10 - 419/2011 vom 6. September 2011 - VD Tribunal cantonal (2011)
RENTE D'INVALIDITÉ, BASE DE CALCUL, REVENU ANNUEL MOYEN | 1 LAI, 36 al. 2 LAI, 69 al. 1 let. a LAI, 29bis al. 1 LAVS, 29quater LAVS, 29quinquies LAVS, 29ter LAVS, 30 al. 2 LAVS, 32 al. 1 RAI, 2 al. 1 let. c LPA-VD, 93 al. 1 let. a LPA-VD